2014
DOI: 10.1371/journal.pone.0110519
|View full text |Cite
|
Sign up to set email alerts
|

Infection with Porphyromonas gingivalis Exacerbates Endothelial Injury in Obese Mice

Abstract: BackgroundA number of studies have revealed a link between chronic periodontitis and cardiovascular disease in obese patients. However, there is little information about the influence of periodontitis-associated bacteria, Porphyromonas gingivalis (Pg), on pathogenesis of atherosclerosis in obesity.Methods In vivo experiment: C57BL/6J mice were fed with a high-fat diet (HFD) or normal chow diet (CD), as a control. Pg was infected from the pulp chamber. At 6 weeks post-infection, histological and immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“… stated a significant association between the increase in some bacterial groups and obesity. Another study reported that dental infection of Porphyromonas gingivalis could contribute to endothelial injury in obese mice . Saito and Shimazaki suggested that the bacterial flora in dental plaque might differ in obese subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… stated a significant association between the increase in some bacterial groups and obesity. Another study reported that dental infection of Porphyromonas gingivalis could contribute to endothelial injury in obese mice . Saito and Shimazaki suggested that the bacterial flora in dental plaque might differ in obese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…They emphasized that obesity did not have a negative impact on the periodontal clinical response after nonsurgical periodontal treatment. Furthermore, Ao et al (42) suggested that periodontal therapy may prevent or minimize the side effects of bacterial infection in obese patients. Our study demonstrated the percentage increase in gingival crevicular fluid and plasma GSH levels of the OCP group compared to the chronic periodontitis group from baseline to post-periodontal treatment, but BMI values did not change.…”
Section: Discussionmentioning
confidence: 99%
“…In other experiments, C57BL/6J mice were made obese by feeding them with a high-fat diet followed by infection with P. gingivalis. It could be demonstrated that the obese mice reacted to infection with more pronounced endothelial injury compared with lean controls and more P. gingivalis bacteria were detected deep in the smooth muscle of the aorta from obese mice [66].…”
Section: Lessons From Animal Modelsmentioning
confidence: 98%
“…Therefore, as a common inflammatory disease, periodontitis may contribute to the development of vascular diseases, resulting in cardiovascular disease (CVD). Although the mechanisms of this relationship have not been fully elucidated, it has been proposed that Pg and LPS can access systemic circulation to cause the breakdown of vascular cells and increase the inflammatory response, which is verified to be the source of CVD risk in patients with periodontal diseases 10 , 11 …”
mentioning
confidence: 99%
“…Although the mechanisms of this relationship have not been fully elucidated, it has been proposed that Pg and LPS can access systemic circulation to cause the breakdown of vascular cells and increase the inflammatory response, which is verified to be the source of CVD risk in patients with periodontal diseases. 10,11 In general, vascular ectopic calcification as a wellknown major risk factor for the adverse CVDs is a highly prevalent vascular pathophenotype that is closely associated with atherothrombotic CVDs, aging, renal failure, and diabetes mellitus. 12 It predicts a worse clinical outcome and major disadvantageous cardiovascular events.…”
mentioning
confidence: 99%